Long-Term Economic Growth: Sources and Prospects - Starkevičiūtė, Margarita; Tabor, Steven R. (Ekonomika, 2000)
Lithuania’s public policy makers arc united in their desire to foster high rates of sustained economic growth through democratic, market-oriented reform. But as the event’ of late 1998 and early 1999 demonstrate, economic growth can he elusive, and can hinge on factors well beyond domestic policy control. In a market economy, the private sector can tap ready sources of growth to expand operations and increase profitability. In so doing, they add value to the domestic economy. The Government can complement private initiative by creating an enabling environment conducive to high-quality, economic growth. Whether or not public policies do, in fact, fost9r growth depends on the sources and impediments to growth prevailing in the economy and the wider constellation of constraint’ and opportunities posed by the global economic setting. How can public policy be crafted to support high-quality economic growth? This paper reviews the sources and prospect’ for long-term economic growth in Lithuania drawing on a number of different approaches and perspectives. Lithuania’s 1990-1994 economic collapse was primarily due to the breakdown of traditional trade relations. rapid adjustment of raw material prices and high rates of inflation. From 1994 to 1998, the economic recovery was led by export growth, a widening savings-investment gap, resource shifts into higherproductivity services activity and, from 1997 onwards, buoyant consumer demand. Enterprises rated the acquisition of market-oriented skills as the single-most important determinant of growth during the recovery period. Growth has been stimulated by cost-reduction (or an improvement in total factor productivity) far more than by factor augmentation. Qualityadjusted labor supply ha, made little contribution to aggregate growth. On average, the contribution of capital investment to growth during 1995-1997 ha, been modest. The larger firms rely more heavily on capital investment as a source of growth, hut rates of total factor productivity improvement in these large firms arc disappointing indeed. The regression results indicate that Lithuania’s enterprise sector is split between two very different types of enterprises. At one extreme arc the big companies that haven’t yet been restructured hut arc relatively successful at attracting investment and staking claims on government resources. These firms arc generating negative value added, and arc witnessing a decline in factor productivity. At the other extreme arc the small, nimble. private enterprises. These arc generating most of the growth in value-added and they arc doing it by raising factor productivity. They tend to he in the services and construction sectors, areas that were ripe for new start-ups in the early 1990s. These results also suggest that in the first stage of transition, private investment is modest and expensive (investors demand a high premium for risk). Economic growth is stimulated more by factors related to human capital (the acquisition of the knowledge and skills needed to work in market conditions and the ability to find new markets, enter into new relations) which results in an increase in total factor productivity. After the macroeconomic situation stabilizes. and transition reforms deepen, capital inflows accelerate. But if these investments arc inefficient, they don’t lead to sustained economic growth, hut to the accumulation of macroeconomic imbalances. Ali a result, modest rates of return on capital will make the large companies less attractive to investors. and the growth of these enterprises slows. A sustainable rate of growth can he maintained if total factor productivity (TFP) continues to improve. This requires a wide range of learning, technology adoption, market development and managerial improvement, a’ a prerequisite to efficient private investment and appropriate enterprise restructuring. Public policy in support of economic growth has been fixated on stimulating private investment. This is clearly a mistake, especially since so much of the investment undertaken by the larger enterprises isn’t contributing either to growth or to TFP improvement. Government has been reticent to correct macroeconomic imbalances, for fear of either curbing private investment or choking private consumption growth. The 1994 to 1998 experience demonstrates the importance of macro-economic stability and an outward orientation to sustained growth. Efforts arc needed to restore macro-economic balances to a sustainable level before financial stability is threatened. Public policy should correct the hi as against labor, and in favor of capital investment, in the tax system. Excessively generous treatment of capital investment and of the wealthy asset holders. does little to stimulate efficient investment. and, in fact, discourages investment in human-capital and TFPenhancing innovations. Reducing the tax wedge against labor and eliminating policies that provide capital-subsidies to poorly performing enterprises (both in heavy industry and agriculture) will help to correct Government’s pro-investment bias. Stimulating savings. rather than promoting (wasteful, state-directed) private investment, should he the main macroeconomic initiative for an economy that needs to enhance TFPgrowth and reduce its external imbalance. Rather than use its scarce resources to tip the balance in favor of private capital investment, the Government should invest in public goods and services that will augment TFP growth. Efficient and effective provision of social services. economic infrastructure and an impartial commercial judiciary arc needed to complement private initiative. To compete globally. Lithuania must continue to improve its gateway status, both in terms of physical infra structure. hut more-so in terms of the foreign languages. information superhighway. travel opportunities and cultural awareness needed to do business worldwide. Public policy should build on the steady progress registered by Lithuania’s small enterprises. Deregulation, together with a policy of zero-tolerance with respect to corruption and organized crime, will significantly enh.mce the enabling environment for small and medium-sized enterprise activity. Reducing the tax wedge on labor will encourage SME’s to expand employment and to avoid the gray economy, both of which will generate positive effects beyond those enjoyed by the SME itself.